2016
DOI: 10.1038/srep32168
|View full text |Cite
|
Sign up to set email alerts
|

The chorioallantoic membrane (CAM) assay for the study of human bone regeneration: a refinement animal model for tissue engineering

Abstract: Biomaterial development for tissue engineering applications is rapidly increasing but necessitates efficacy and safety testing prior to clinical application. Current in vitro and in vivo models hold a number of limitations, including expense, lack of correlation between animal models and human outcomes and the need to perform invasive procedures on animals; hence requiring new predictive screening methods. In the present study we tested the hypothesis that the chick embryo chorioallantoic membrane (CAM) can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
80
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 91 publications
(86 citation statements)
references
References 51 publications
1
80
1
2
Order By: Relevance
“…In agreement with our previous study (Moreno‐Jiménez et al, ), we demonstrated that CAM‐implantation of human viable bone cylinders resulted in a significant increase in bone volume (9.79% ± 2.24 SD ; p <0.001). The pre‐existing mineralised tissue of the bone cylinder prevented the quantification or visualisation of the newly formed bone alone.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…In agreement with our previous study (Moreno‐Jiménez et al, ), we demonstrated that CAM‐implantation of human viable bone cylinders resulted in a significant increase in bone volume (9.79% ± 2.24 SD ; p <0.001). The pre‐existing mineralised tissue of the bone cylinder prevented the quantification or visualisation of the newly formed bone alone.…”
Section: Discussionsupporting
confidence: 93%
“…Using our previously published protocol (Moreno‐Jiménez et al, ), we implanted freshly isolated human bone cylinders on the CAM and were able to measure increases in bone volume following incubation. CAM‐implanted bone cylinders displayed a significant increase (9.79% ± 2.24 SD ; n = 6–8; p 0.001) compared with in vitro ‐cultured bone cylinders (1.60% ± 1.06 SD) and control (−0.19% ± 0.33 SD ; bone cylinders maintained at 4 °C) from the same donor.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations